Effect of low protein diets and lysine supplementation on growth performance and carcass characteristics of growing pigs - A. Kumar; R. Bhar,A. B. Mandal; S. K. Mendiratta (African Journal of Pig Farming, 2019)
The present study was to assess the effect of feeding low protein diet with or without supplemental lysine to meet NRC (1998) requirement on growth performance, carcass trait, meat composition, and meat quality of pigs. An experiment of 126 days was conducted on 21 crossbred Landrace pigs (average weight 11.72 ± 0.57 kg, average age 7.59 ± 0.14 weeks). Animals were randomly assigned to three dietary treatment groups T0, T1 and T2 each comprising 7 animals. A basal diet (T0) was formulated as per NRC (1998). Basal diet (T1) reduced crude protein by 10% with supplemental lysine identical in T0; while without supplemental lysine in T2 (that is, reduced protein by 10% and lysine by 15%). All the diets were iso-caloric and offered in phases according to change in body weight (10 to 20, 20 to 50, 50 to 80 and >80 kg). Growth performance, carcass parameters, meat composition and meat quality were evaluated at the end of the trial on four animals per group. The results show no significant difference on growth parameters and carcass and meat quality traits among the groups. Thus, it was concluded that the crude protein and lysine concentration can be reduced safely by 10 and 15%, respectively to that of NRC (1998) in diet of crossbred Landrace pigs without any compromise on performance during growing and fattening stage of production.